Gam Gam - Samuel, Natacha; Klockenbring, Florent (France : ShellacSud - Les films Serendipity, 2015)
Karim lives in Brest and works at the local airport. Every two years he returns to Ouagadougou, the capital of Burkina Faso, to be with his family and friends and must confront those who never left. This film traces the breaking point between those that left and those that stayed in Ouagadougou.
Verzio Film Festival Submission
Keywords: Documentary films